Expression of CD90 decreases with progression of synovial chondromatosis in the temporomandibular joint. Issue 4 (3rd July 2016) - Wake, So; Yoshitake, Hiroyuki; Kayamori, Kou; Izumo, Toshiyuki; Harada, Kiyoshi
Abstract : Objectives: The aim of the present study was to investigate the factors that contribute to the progression of synovial chondromatosis in the temporomandibular joint (TMJ). Methods: The authors investigated the expression of CD105 and CD90 in specimens from 17 patients with synovial chondromatosis in the TMJ, using immunohistochemical staining, and expression of CD105 and CD90 in cartilaginous nodules was scored semiquantitatively. Results: The expression of CD105 and CD90 was found in almost all the cases. In particular, the expression of CD90 in cartilaginous nodules significantly decreased with the progression of synovial chondromatosis. Discussion: The factors that determine progression of synovial chondromatosis are not fully understood. The results of this study suggest that CD90 may play an important role in the progression of synovial chondromatosis in the TMJ.